2017
DOI: 10.1002/glia.23276
|View full text |Cite
|
Sign up to set email alerts
|

Activation of EP2 receptor suppresses poly(I: C) and LPS‐mediated inflammation in primary microglia and organotypic hippocampal slice cultures: Contributing role for MAPKs

Abstract: Brain inflammation is a critical factor involved in neurodegeneration. Recently, the prostaglandin E (PGE ) downstream members were suggested to modulate neuroinflammatory responses accompanying neurodegenerative diseases. In this study, we investigated the protective effects of prostaglandin E receptor 2 (EP ) during TLR3 and TLR4-driven inflammatory response using in vitro primary microglia and ex vivo organotypic hippocampal slice cultures (OHSCs). Depletion of microglia from OHSCs differentially affected T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 72 publications
3
21
0
Order By: Relevance
“…It has been reported that primary microglia can be activated by 10 ng/ml LPS [ 46 , 47 ]. In our in vitro experiments, primary microglia were pretreated with 10 μM H2R/H3R agonists 30 min before exposure to 10 ng/ml LPS.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that primary microglia can be activated by 10 ng/ml LPS [ 46 , 47 ]. In our in vitro experiments, primary microglia were pretreated with 10 μM H2R/H3R agonists 30 min before exposure to 10 ng/ml LPS.…”
Section: Discussionmentioning
confidence: 99%
“…Different stimuli may lead to increased expression of microglia TLRs, such as hypoxia (Smith et al, 2013 ; Yao et al, 2013 ), LPS (Kielian et al, 2005 ; Yousif et al, 2018 ), Poly(I:C; Yousif et al, 2018 ), kainic acid (Wang et al, 2015 ; Hu and Mao, 2016 ), α-synuclein (Béraud et al, 2011 ; Daniele et al, 2015 ) and amyloid beta (Aβ; Jana et al, 2008 ; Richard et al, 2008 ; Caldeira et al, 2017 ).…”
Section: Tlr Expression In the Cnsmentioning
confidence: 99%
“…TLR3 is less studied in respect to neurodegenerative diseases, although it may be involved in neuroinflammation. For example, incubation of microglia with Poly(I:C), a TLR3 agonist, increases the synthesis of COX-2, mPGES-1 and prostaglandin E 2 release (de Oliveira et al, 2016 ), and increased the expression of TLR3 (Yousif et al, 2018 ). The production of these inflammatory mediators might contribute to neurodegenerative processes observed in some conditions.…”
Section: Tlr3mentioning
confidence: 99%
“…Cyclooxygenase-2 (COX-2), the inducible form of COX, is dynamically regulated by synaptic activities, 1 and is rapidly upregulated in the brain after cerebral ischemia 2,3 and other neurological insults. 412 As a major enzymatic product of COX2 in the cerebral cortex, prostaglandin E2 (PGE 2 ) can activate four G protein-coupled receptors (GPCRs) named EP1 through EP4, that together regulate a myriad of physiological and pathological signaling events. For instance, the EP1 receptor is coupled to G α q that mediates the mobilization of cytosolic Ca 2+ , resulting in the activation of protein kinase C (PKC); EP2 and EP4 are associated with G α s that activates adenylyl cyclase, leading to cAMP-dependent signaling; EP3 is mainly coupled to G α i and its activation downregulates cytosolic cAMP.…”
Section: Introductionmentioning
confidence: 99%